Impact of Competition Anxiety, Personality Traits on Wushu and Judo Players: An Investigation into the Impact of Personality Traits and Competition Anxiety on Wushu and Judo Players (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Nowadays in sports field the role of abilities and psychosomatic preparations of sportspersons in sport successes and achieving desire performance in competitions and tournaments, even in some circumstance, be considered more important than the technical preparation. Sports like Wushu and Judo are gaining popularity throughout the world because of its unique qualities, which have entices a large number of people to participate in these events every year. The reason for the investigation is to break down the impact on Wushu and Judo players of aggression, competition anxiety, achievement pressure, personality traits, and self-concept. A sum of 200 players, for example 100 Wushu players and 100 Judo players from different Rajasthan colleges were chosen to accomplish the reason for the examination. Hundred players who addressed their school gathering and partook in the competition between school levels were chosen from the topics picked, for example, 50 Wushu players and 50 Judo players and 100 players who addressed their school gathering and took an interest in the competition between school levels, for example, 50 Wushu players and 50 Judo players. The subjects went in age from 18 years to 22 years. To discover the critical variation between various levels of Wushu and Judo players on state anxiety, attribute anxiety, aggression and neuroticism, a two-way (2x2) change examination of the autonomous gathering was applied. Since two gatherings and two unmistakable test levels were thought about, the Scheffe's test was applied as a post hoc test to decide the combined mean contrasts, assuming any, when they got 'F' proportion an incentive in the basic impact test was huge. Factual hugeness at .05 levels was fixed in all cases.